Role of Small States in International Relations Comparative Analysis of the Czech Republic and Israel - Hlavsová, Aneta, 1989-; Sršeň, Radim; Dubský, Zbyněk, 1974-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
This study is titled Role of Small States in International Relations: Comparative Analysis of the Czech Republic and Israel and its main purpose is to analyze a typical small state's behavior in the international arena on the examples of the Czech and Israeli foreign policy. It is divided into four respective sections -- a theoretical framework, historical background, and the two case studies, and it strives to answer a foundational question whether the Czech Republic and Israel can be considered small players in international relations based on the theoretical definition of the notion of a small state as well as the countries' current foreign policy approaches and tools.
Vedoucí práce: Radim Sršeň
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses